Causal relationship between oral performance and communication apprehension - Sham, R.M.; Azmi, M.N.L. (2018)
This study investigates the causal relationship between the form students who have passed in School-Based Oral Evaluation (SBOE) with communication apprehension. The participants are 302 of form four male and female students from the government secondary schools in Putrajaya Federal Territory, Malaysia. The purpose of this study is to determine the effectiveness of SBOE and its relationship with communication apprehension. This study is an explanatory sequential mixed method design in which quantitative and qualitative [11] data were collected in sequential, analyzed separately, and then explained. The quantitative data were collected by using FLCAS, SBOE results and the qualitative data were collected from the semi-structured interviews with the English teachers. The quantitative data were analysed by descriptive analysis (SPSS) and the qualitative data were analysed by content analysis. The results revealed that the students had scored high results in SBOE in the mid-term examination 2017. The findings from the quantitative and qualitative methods showed that students experience low level of communication apprehension. High oral performance affects communication apprehension. This study recommends a new oral-based English curriculum for the secondary schools.